2001
DOI: 10.1103/physrevb.64.054411
|View full text |Cite
|
Sign up to set email alerts
|

Theory of a magnetic microscope with nanometer resolution

Abstract: We propose a theory for a type of apertureless scanning near field microscopy that is intended to allow the measurement of magnetism on a nanometer length scale. A scanning probe, for example a scanning tunneling microscope (STM) tip, is used to scan a magnetic substrate while a laser is focused on it. The electric field between the tip and substrate is enhanced in such a way that the circular polarization due to the Kerr effect, which is normally of order 0.1% is increased by up to two orders of magnitude for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The detailed scheme for calculating G has been described earlier, for example, in Ref. 42. It remains to evaluate the current-current Green's function ⌸ Ͻ (r 1 ,r 2 ,) and to carry out the integrations over the coordinates r 1 and r 2 in Eq.…”
Section: Eementioning
confidence: 99%
“…The detailed scheme for calculating G has been described earlier, for example, in Ref. 42. It remains to evaluate the current-current Green's function ⌸ Ͻ (r 1 ,r 2 ,) and to carry out the integrations over the coordinates r 1 and r 2 in Eq.…”
Section: Eementioning
confidence: 99%
“…17 There have been detailed numerical calculations of the near field associated with apertureless probes, 18,19,20 and the field enhancement has been discussed in the context of apertureless SNOM. 21 In addition, the role of tip geometry, 22,23,24 the influence of tip modulation, 25 and the implications for magneto-optical near-field imaging 26,27 have been studied. Nevertheless, there is a need for clarification of how the tip-sample coupling affects the signal detected and the local-field enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Johansson has also suggested that the enhanced diffuse reflectance is a single particle effect and has pointed out that the externally incident light creates peaks in the local field in the presence of the waveguide, leading to an increase in the diffuse reflectance at these wavelengths. 10 However, Johansson did not consider the role of the scattering cross section of the waveguided light. It can be seen from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8 The diffuse reflectance spectrum has been modeled by Soller, using a convolution of the single particle Green's dyadic with a correlation function for the average properties of the particle distribution, 9 and by Johannson, using a lattice-gas model with averaging over different realizations of the disorder using a coherent potential approximation. 10 However, there has been no model proposed to date to predict the absorptance enhancement in the silicon.…”
Section: Introductionmentioning
confidence: 99%